2013
DOI: 10.1371/journal.pone.0072248
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the C-Terminal Peptide of Pulmonary Surfactant Protein B (SP-B) with a Bicellar Lipid Mixture Containing Anionic Lipid

Abstract: The hydrophobic lung surfactant SP-B is essential for respiration. SP-B promotes spreading and adsorption of surfactant at the alveolar air-water interface and may facilitate connections between the surface layer and underlying lamellar reservoirs of surfactant material. SP-B63–78 is a cationic and amphipathic helical peptide containing the C-terminal helix of SP-B. 2H NMR has been used to examine the effect of SP-B63–78 on the phase behavior and dynamics of bicellar lipid dispersions containing the longer cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
4
4
0
Order By: Relevance
“…In particular, the spectrum at the transition is a superposition of spectral components from the two coexisting phases. In an earlier study using DMPC- d 54 /DMPG/DHPC (3:1:1), it was reported that SP-B 63–78 lowers the temperature for the transition from the magnetically orientable phase to the extended lamellar phase in lipid dispersions with this composition . The spectra of DMPC- d 54 /DMPG/DHPC (3:1:1) with 10% (w/w) SP-B 63–78 shown in Figure b are consistent with this observation.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…In particular, the spectrum at the transition is a superposition of spectral components from the two coexisting phases. In an earlier study using DMPC- d 54 /DMPG/DHPC (3:1:1), it was reported that SP-B 63–78 lowers the temperature for the transition from the magnetically orientable phase to the extended lamellar phase in lipid dispersions with this composition . The spectra of DMPC- d 54 /DMPG/DHPC (3:1:1) with 10% (w/w) SP-B 63–78 shown in Figure b are consistent with this observation.…”
Section: Resultssupporting
confidence: 80%
“…In an earlier study using DMPC-d 54 /DMPG/DHPC (3:1:1), it was reported that SP-B 63−78 lowers the temperature for the transition from the magnetically orientable phase to the extended lamellar phase in lipid dispersions with this composition. 39 The spectra of DMPC-d 54 /DMPG/DHPC (3:1:1) with 10% (w/w) SP-B 63−78 shown in Figure 3b are consistent with this observation. The peptide-induced lowering of the magnetically orientable to extended lamellar phase transition has been interpreted as indicating that, for bicellar mixtures with an anionic long-chain lipid component, SP-B 63−78 promotes coalescence to the more extended lamellar phase at a lower temperature than in the absence of peptide.…”
Section: ■ Results and Discussionsupporting
confidence: 79%
See 3 more Smart Citations